Distribution of Necromass under Different Forest Stands in a Savannah Ecosystem - , Ebenezer Djaney Djagbletey; , Charles Quansah; , Gloria Djaney Djagbletey; , Henry Oppong Tuffour; , Awudu Abubakari (Archives of Current Research International, 2016)
The amount of environmental issues related to the loss of forest cover resulting from anthropogenic perturbations leading to low levels of production, and in consequence, intensification and increased deforestation are serious concerns in Ghana, especially in the Savanna Agro-ecological zones. The actual study was, however, carried out in Kenikeni, Sinsablegbinni and Klupene forest reserves. Using a randomly laid numbered 1 km x 1 km grid, which was sub-divided into sixteen sub-plots of 25 m x 25 m, the Nested Plot Design was employed in demarcating zones in each forest reserve for the study. In general, five plots were selected to constitute the Nested Plot in each reserve. Overall, the results showed that necromass C stock was in the order of Klupene forest (0.291 Mg C/ha) > Sinsablegbinni (0.136 Mg C/ha) > Kenikeni (0.090 Mg C/ha). The differences in necromass C stock among the various forests showed that the accumulation of necromass was higher in Klupene forest.